Dynamic reliability management: Reconfiguring reliability-levels of hardware designs at runtime - Anwer, Jahanzeb; Meisner, Sebastian; Platzner, Marco (Reconfigurable Computing and FPGAs (ReConFig), 2013 International Conference on)
Keywords: fault tolerant computing; field programmable gate arrays; logic design; reliability; BYU-LANL tool; DRM tool flow; FPGA based hardware designs; avionic application; device technologies; dynamic reliability management; fault-tolerant operation; hardware designs; reconfiguring reliability levels; space applications; Field programmable gate arrays; Hardware; Redundancy; Reliability engineering; Runtime; Tunneling magnetoresistance

An Approach for Self-Reconfiguring and Fault-Tolerant Distributed Real-Time Systems - Klobedanz, Kay; Müller, Wolfgang; Rettberg, Achim
In this paper we present an approach for the self reconfiguration of distributed micro-controllers for increased fault tolerance. Based on a modified distributed system topology utilizing a time division multiple access (TDMA) protocol, i.e., Flex Ray, we present a self-organized distributed coordinator concept which performs the self-reconfiguration in the case of node failures. We introduce a distributed coordinator, which utilizes redundant slots in the Flex Ray communication schedule and combines messages in configured protocol frames and slots to avoid a complete bus restart. As such, the self-reconfiguration is realized by means of predetermined information about resulting changes in the communication dependencies and (re-)assignments determined in the design phase. To retrieve the necessary information, we present an analytical approach, which determines a combined solution for the initial configuration and all possible reconfigurations for the remaining nodes of the Flex Ray network in case of node failures. Hence, through this method we can design self-reconfiguring network-based systems enabling the handling of node failures for an increased fault tolerance.
Keywords: Real time systems; Fault tolerant systems; Schedules; Protocols; Redundancy; Delay

A Reconfiguration Approach for Faul-Tolerant FlexRay Networks - Klobedanz, Kay; König, Andreas; Müller, Wolfgang (Proceedings of DATE'11)
In this paper we present an approach for the configuration and reconfiguration of FlexRay networks to increase their fault tolerance. To guarantee a correct and deterministic system behavior, the FlexRay specification does not allow a reconfiguration of the schedapproachule during run time. To avoid the necessity of a complete bus restart in case of a node failure, we propose a reconfiguration using redundant slots in the schedule and/or combine messages in existing frames and slots, to compensate node failures and increase robustness. Our approach supports the developer to increase the fault tolerance of the system during the design phase. It is a heuristic, which, additionally to a determined initial configuration, calculates possible reconfigurations for the remaining nodes of the FlexRay network in case of a node failure, to keep the system working properly. An evaluation by means of realistic safety-critical automotive real-time systems revealed that it determines valid reconfigurations for up to 80% of possible individual node failures. In summary, our approach offers major support for the developer of FlexRay networks since the results provide helpful feedback about reconfiguration capabilities. In an iterative design process these information can be used to determine and optimize valid reconfigurations.
Keywords: Schedules; Fault tolerant systems; Redundancy; Protocols; Automotive engineering; Genetic algorithms

Distributed Coordination of Task Migration for Fault-Tolerant FlexRay Networks - Klobedanz, Kay; Defo, Gilles B.; Müller, Wolfgang; Kerstan, Timo (Proceedings of SIES 2010)
In this paper we present an approach to increase the fault tolerance in FlexRay networks by introducing backup nodes to replace defect ECUs (Electronic Control Units). In order to reduce the memory requirements of such backup nodes, we distribute redundant tasks over different nodes and propose the distributed coordinated migration of tasks of the defect ECU to the backup node at runtime. This approach enhances our former work in, where we extended the FlexRay bus schedule by redundant slots to consider changes in the communication/slot assignment and investigated and evaluated different solutions to migrate the redundant tasks to the backup node using the static and/or dynamic segment of the communication cycle for transmissions. We present the approach of distributed coordination for migration and communication instead of additional dedicated coordinator nodes to further increase the fault tolerance. With this approach we improve the safety of FlexRay networks by avoiding a possible single point of failure due to a dedicated coordinator node also minimizing the necessary time needed for a reconfiguration after an ECU failure. Furthermore, we reduce the overhead within the communication and the demand for additional hardware components.
Keywords: Fault tolerant systems; Protocols; Redundancy; Runtime; Payloads; Schedules